2012
DOI: 10.11130/jei.2012.27.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Regional Integration and Real Convergence: Evidence from MENA Countries

Abstract: This article analyses and explains the real convergence process in MENA countries over the past 50 years. It provides a threefold contribution. Firstly, given the recent increasing attention paid to the Euro-Mediterranean area, it focuses on the convergence of MENA countries towards the EU per capita income. Second, it provides an econometric modelling of the determinants of convergence. Finally, it is based on a wide set of convergence indicators applied to various measures of per capita income as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…First, we have adopted a robust methodology (including a battery of panel unit root and cointegration tests) to estimate the share of capital in total output, in contrast to the previous studies which used a prior share of capital. Second, we used improved notions of convergence that utilize the time series property of the variables under investigation, like stochastic and deterministic convergence tests, whereas the majority of the previous studies have employed conventional tests of beta-convergence ( β -convergence) and sigma-convergence ( σ -convergence) (Andreano et al, 2013; Guetat & Serranito, 2007; Péridy & Bangoulla, 2012). Furthermore, we investigated the convergence in the sources of output per worker, such as physical capital per worker, human capital and TFP.…”
Section: Introductionmentioning
confidence: 99%
“…First, we have adopted a robust methodology (including a battery of panel unit root and cointegration tests) to estimate the share of capital in total output, in contrast to the previous studies which used a prior share of capital. Second, we used improved notions of convergence that utilize the time series property of the variables under investigation, like stochastic and deterministic convergence tests, whereas the majority of the previous studies have employed conventional tests of beta-convergence ( β -convergence) and sigma-convergence ( σ -convergence) (Andreano et al, 2013; Guetat & Serranito, 2007; Péridy & Bangoulla, 2012). Furthermore, we investigated the convergence in the sources of output per worker, such as physical capital per worker, human capital and TFP.…”
Section: Introductionmentioning
confidence: 99%
“…Pé ridy et al [65] conducted a comprehensive study on climate change in the MENA region, revealing alarming consequences. They found that these countries are the most affected by the negative consequences of climate change.…”
Section: The General Scope Of the Mena Countriesmentioning
confidence: 99%
“…Our study has extended this by considering more variables that comprise the GCC convergence criteria and the OCA theory. Péridy and Bagoulla (2012) analysed and explained the real convergence process in MENA countries over a period of 50 years, focusing on the convergence of MENA countries towards the EU per capita income. Their results showed that despite a lack of s-convergence for the MENA region taken as a whole, the convergence hypothesis was accepted using the g and β-convergence tests, especially for Tunisia, Egypt, Turkey, and Morocco but evidence showed divergence for Jordan and Algeria.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%